KADAR CO ( KARBON MONOKSIDA ) PADA RUANGAN PARKIR BAWAH TANAH DI MALL GALERIA YOGYAKARTA - -, Warniningsih (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2010)
Galeria Mall Jogjakarta is one of the shopping centres with underground parking lot. The CO (carbon monoxide) influences visitors and workers within. Known that the room could be fatal, the basement is not fulfilled with air channels so that the exhaust gas vehicles trapped in the parking space itself. Those, will eventually cause disturbance to human health. Therefore research is needed to determine how far the levels of CO (carbon monoxide) in the parking lot in the mall land. Research methods includes the way of measurement of CO levels, temperature, humidity, wind speed and the number of vehicles from 09.30 - 14.30. The samples were taken for analysis (CO), Thermoter (temperature), Anemometer (wind speed) and Pyrometer (moisture). The study areas were including motorcycle parking areas, the midde of motorcycle and car parking areas and the last is the car parking areas. Result of the research is average level of CO pollution ranged from 16,100 to 19,550 Î¼g/m3 at 09.30 A.M by the number of motor vehicles and cars are 49, while from 12:00 to 14:30 A.M between 34,116.67 to 45,616.67 Î¼g/m3 with a number of motor vehicles and cars we 544. The conclusion of the study is that between 12-14.30 A.M there was CO standard normal overload within the underground parking areas of Galeria Mall. Re study of the facilities is required, sonly.